FIRM VALUE IN THE NON-CYCLICALS CUSTOMER SECTOR: PROFITABILITY AND FIRM SIZE - Sasiska Rani; Aida Rakhmawati; Pipit Fitri Rahayu; Alven Arisandi (Jurnal Kompetitif, 2023)
This research aims to examine the effect of profitability and firm size on firm value in non-cyclical sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The population in this study is 87 companies. The sampling technique used was purposive sampling, so 26 companies were obtained as samples. The analysis technique used in this research is multiple linear regression analysis. The research results show that partially profitability has an effect on firm value and firm size has no effect on company value.